PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS VIDEO ANIMASI BERBANTUAN APLIKASI DORATOON UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Adek Nilasari Harahap; Nuraisyah Nuraisyah; Nurdalilah Nurdalilah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2026)
The problem identified in class X-2 of SMA Negeri 1 Angkola Timur was the low learning interest of students in mathematics. To address this issue, a research and development study was conducted by creating an animation-based video learning medium using the Doratoon application. The aim of this study was to enhance students’ learning interest through more engaging media. The research employed the ADDIE development model developed by Dick and Carey. Prior to implementation, the learning media was validated by media experts and material experts, resulting in scores of 79% and 89% respectively. According to the eligibility criteria, the product was declared valid. Furthermore, a trial was conducted with 24 students of class X-2, yielding a score of 81%. Thus, the animation-based video learning medium was proven to be feasible for use in mathematics learning, to facilitate material delivery, and to effectively increase students’ learning interest.